Managing High-Technology Programs and Projects, Third Edition - D.Archibald Russell (American : Wiley, 2003)
PROJECTmagazine, Spring 2004
"...by far the most comprehensive, practical and easy to understand reference book on project management principles..."
Project Management World Today, March-April 2004
"...unique among project management literature...define(s) an integrated path to improved project performance and success."
Contents
Part 1: Executive guide to progam and project management
1.Excutive overview of project management
2.Progams and Projects
3.Improving Project management Capabilities
4.Intergrative Roles in project management
5.Intergrative and Predictive Project planning and control
6.Project team and key human aspects of project management
7.Organizing the Project management function
8.Managing project Portfolios, programs, and multiple projects
Part II : Managing specific projects
9.Organizing the individual project office and project team
10.Planning and Intitiating projects
11. Project team planning and project stast-up
12.Authorizing and controlling the work, schedula, and costs
13.Project Interface management
14.Evaluating, Directing, and Closing out the project
Keywords: Project management; High technology